Mapping Skills Assessment through Skills Bio-chart Data Analytics - Soon, E.H.; Baharun, S.; Mahrin, M.N.; Abdul manaf, N. (INTI International University, 2018)
This paper presents the concept of the Skills Bio-chart as a novel method to measure progressive growth pathway for skills assessment in Malaysia, particularly targeting the Technical and Vocational Education and Training (TVET) stream. The architecture of the Skills Bio-chart is designed using graph theory mapping in line with two key constructs, which is the learning outcome domains (LOD) of the Malaysian Qualifications Framework (MQF) and the competency framework of the National Occupancy Skills Standards (NOSS). The extended mapping of predefined skill sets integrates with the LOD components which correlate to the NOSS competency matrix to form multiple factorial graph connection. Sampling only from the Information and Communications Technology (ICT) sector under the NOSS subset, the analytics in this paper is limited to only the certificate level (Level 1 to Level 3) of TVET and skills education. The user interface (UI) of the Skills Bio-chart is incorporated into the Skills Biometrics Service Platform which serves as a customized online learning database platform that functions as the backend support unit. Additionally, this paper presents the factor analysis on the acceptance of the Skills Bio-chart model as a significant competency measurement tool through the Technology Acceptance Model (TAM) testing